Influence of tillage methods on the development of wheat diseases Aestivum and Fontum - A. V. Ponomarev; O. Yu. Kremneva; K. E. Gasiyan; R. Yu. Danilov (Юг России: экология, развитие, 2022)
Aim. To analyze the data in the available literature regarding the effect of various tillages on the development and prevalence of wheat pathogens.Discussion. According to the literature, the existing tillage technologies – classical, minimal and zero – significantly affect the development of pathogens that cause the development of wheat diseases in regions that differ in soil and climatic conditions. In Russia and other countries near and far, the issue of combating diseases of agricultural crops is dealt with by chemical, biological and agrotechnical methods. Despite the fact that agrotechnical methods are of the utmost importance in the general system of measures to protect plants from damage, for a long‐time agricultural technology as a means of plant protection was underestimated. However, many agricultural techniques, as well as genetics and selection, increase the resistance of plants to damage.Conclusion. As a result of these techniques, it is possible to create environmental conditions that will be unfavourable for the reproduction of diseases. At the present time, opinion is firmly established that separately undertaken, isolated methods cannot properly solve the problem of protecting plants from pathogens of agricultural crops. Only a set of methods combined into a system of measures provides a solid basis for plant protection. And in this system of measures, the role of agricultural practices is extremely large.